2023
DOI: 10.3892/etm.2023.12183
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B induces apoptosis in colorectal cells through reactive oxygen species generation and endoplasmic reticulum stress pathways

Jian-Lan Huang,
Li Liang,
Pei-En Xie
et al.

Abstract: Cucurbitacin B (CuB) is a member of the cucurbitacin family, which has shown potent anticancer pharmacological activity. Prolonged or severe endoplasmic reticulum stress (ERS) induces apoptosis; therefore, the present study investigated whether CuB may activate the ERS pathway to induce apoptosis. HT-29 and SW620 colorectal cancer (CRC) cells were treated with a range of concentrations of CuB for 48 h, and the viability and proliferation of cells were determined using Cell Counting Kit 8 (CCK8) and colony form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Cucurbitacin, triterpenoid including cucurbitacin B and cucurbitacin E, are triterpenoids from the cucurbitaceae family Cucumis melo L., which have therapeutic effects on a wide range of tumors ( Hong T et al, 2023 ; Hsu HL et al, 2023 ; Yang Y et al, 2023 ). Huang JL et al (2023) found that cucurbitacin B (0.005, 0.01, 0.05, 1, 5, 10, 20, 40, 100 μM for 48 h) inhibited the proliferation and induced apoptosis of CRC cells HT-29 and SW620 by concentration-dependently increasing the protein expression of p-PERK, p-eIF2α, ATF4, IRE1α and XBP1. After CHOP knockdown, the apoptosis rate was significantly decreased.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 97%
See 3 more Smart Citations
“…Cucurbitacin, triterpenoid including cucurbitacin B and cucurbitacin E, are triterpenoids from the cucurbitaceae family Cucumis melo L., which have therapeutic effects on a wide range of tumors ( Hong T et al, 2023 ; Hsu HL et al, 2023 ; Yang Y et al, 2023 ). Huang JL et al (2023) found that cucurbitacin B (0.005, 0.01, 0.05, 1, 5, 10, 20, 40, 100 μM for 48 h) inhibited the proliferation and induced apoptosis of CRC cells HT-29 and SW620 by concentration-dependently increasing the protein expression of p-PERK, p-eIF2α, ATF4, IRE1α and XBP1. After CHOP knockdown, the apoptosis rate was significantly decreased.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 97%
“…Nobiletin, a flavonoid from the botanical drug Pericarpium Citri Reticulatae and its variants, has a variety of biological effects such as antithrombotic, anti-inflammatory and antioxidant ( Geng YZ et al, 2023 ; Huang L et al, 2023 ). Chen M et al (2023) found that nobiletin inhibited the proliferation of GC cells HGC-27 and MKN-28, which may be mediated through the activation of IRE-1α/GRP78/CHOP axis.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%
See 2 more Smart Citations